2015
DOI: 10.1103/physreve.91.022904
|View full text |Cite
|
Sign up to set email alerts
|

State transition induced by higher-order effects and background frequency

Abstract: State transition between the Peregrine rogue wave and w-shaped traveling wave induced by higherorder effects and background frequency is studied. We find that this intriguing transition, described by an exact explicit rational solution, is consistent with the modulation instability (MI) analysis that involves MI region and stability region in low perturbation frequency region. In particular, the link between the MI growth rate and transition characteristic analytically demonstrates that, the size characteristi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 49 publications
2
68
1
Order By: Relevance
“…8(b), a stable broad spectrum of the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT W-shaped soliton by letting b → 0 is presented. This is consistent with spectrum properties of the state transitions induced by the higher-order effects in [29].…”
Section: Spectrum Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…8(b), a stable broad spectrum of the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT W-shaped soliton by letting b → 0 is presented. This is consistent with spectrum properties of the state transitions induced by the higher-order effects in [29].…”
Section: Spectrum Analysissupporting
confidence: 86%
“…Additionally, recent hydrodynamical experiments and theoretical research confirm that the "super rogue waves" could be simulated by higher-order rational solutions [15][16][17][18][19][20][21][22][23][24][25][26][27]. More recently, with resort to the modulation instability (MI) analysis, state transition between brether/rogue wave and W-shaped soliton in high-order system, and state transition among different types of rogue-wave patterns in coupled system have been strictly demonstrated [28][29][30].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Wang et al [43,44] have found that the breather solutions of the fourth-order NLS and variable-coefficient Hirota equations can be converted into four types of nonlinear waves on constant backgrounds, including the multi-peak solitons, antidark soliton, periodic wave and W-shaped soliton. Liu et al [45,46] have discovered that state transitions between the Peregrine rogue wave and W-shaped travelling wave in the Hirota as well as the coupled Hirota equations appear as a result of higher-order effects. For the Sasa-Satsuma equation with the third-order dispersion, self-steepening and delayed nonlinear response, the high-order effects could make the rogue waves twisted [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…The striking process involves both MI and modulation stability (MS) regimes, in contrast to the rogue waves and W-shaped soliton reported before which involve MI and MS [49], respectively. Indeed, with certain higher-order perturbation terms such as the third-order dispersion and delayed nonlinear response term, the MI growth rate shows a non-uniform distribution characteristic in the low perturbation frequency region, in particular, it opens up a stability region as the background frequency changes [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Manakov system and coupled Hirota equations) with interacting wave components of different amplitudes and frequencies [26][27][28] have been of continued interest. Most recently, Akhmediev and one of the authors Liu show that the higher-order integrable perturbations and coupled-wave interaction can indeed generate state transition effects from breather/rogue wave to W-shaped soliton [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%